2003
DOI: 10.1136/gut.52.10.1494
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SRD5B1 (AKR1D1), the gene encoding  4-3-oxosteroid 5 -reductase, in hepatitis and liver failure in infancy

Abstract: Background: A substantial group of patients with cholestatic liver disease in infancy excrete, as the major urinary bile acids, the glycine and taurine conjugates of 7a-hydroxy-3-oxo-4-cholenoic acid and 7a,12a-dihydroxy-3-oxo-4-cholenoic acid. It has been proposed that some (but not all) of these have mutations in the gene encoding D 4 -3-oxosteroid 5b-reductase (SRD5B1; AKR1D1, OMIM 604741). Aims: Our aim was to identify mutations in the SRD5B1 gene in patients in whom chenodeoxycholic acid and cholic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 35 publications
1
85
0
1
Order By: Relevance
“…AKR1D1 genetic variations were also reported in three patients with neonatal onset cholestatic liver disease. These patients had rare disease causing AKR1D1 genetic variation that was not detected in 100 chromosomes of control individuals indicating that these are disease-specific mutations (Lemonde et al, 2003). Our study did identify a common 39-UTR SNP (rs1872930) genotype that correlated significantly with total hepatic AKR1D1 and P450 mRNA expression.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…AKR1D1 genetic variations were also reported in three patients with neonatal onset cholestatic liver disease. These patients had rare disease causing AKR1D1 genetic variation that was not detected in 100 chromosomes of control individuals indicating that these are disease-specific mutations (Lemonde et al, 2003). Our study did identify a common 39-UTR SNP (rs1872930) genotype that correlated significantly with total hepatic AKR1D1 and P450 mRNA expression.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, we tested whether genetic variation in AKR1D1 was associated with P450 mRNA expression and activity. To date, genetic variation in AKR1D1 has not been explored in normal individuals, and rare genetic variants have been reported only in infants that lack cholic acid and chenodeoxycholic acid (Lemonde et al, 2003). In this study, we report that genetic variation in AKR1D1 contributes to the observed variation in P450 expression and activity of the P450 liver network.…”
Section: Introductionmentioning
confidence: 64%
“…The resulting 5β-dihydrosteroids are further reduced by liver AKR1C4 to ultimately form chenodeoxycholic and cholic acids. Mutations in the gene encoding AKR1D1 (also known as SRD5B1) in human patients lead to neonatal cholestasis, hepatitis, and liver failure (Lemonde et al, 2003;Setchell et al, 1988). AKR1D1 also exhibit enzymatic activity for several steroid hormones including testosterone, progesterone, cortisol and cortisone among others (Okuda and Okuda, 1984) and is present in the brain (Hutchison and Steimer, 1981) and in tissues of the genitourinary tract.…”
Section: Akr1d1 -Delta 4-3-ketosteroid-5-beta-reductasementioning
confidence: 99%
“…The letters used are based on order of discovery. The number of non-synonymous SNPs in the coding regions of human AKRs so far reported are listed in parenethesis: AKR1A1 (2); AKR1B1 (8); AKR1B10 (3); AKR1C1 (3); AKR1C2 (10); AKR1C3 (9); AKR1C4 (5); AKR1D1 (although none are listed, inherited mutations are associated with bile acid deficiency [109][110][111][112]); AKR7A2 (8) and AKR7A3 (3). Since the crystal structures of many of these AKRs are available these SNPs can be mapped to these structures to predict their functional consequences.…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%